Beyond PEG2000: Synthesis and Functionalisation of Monodisperse PEGylated Homostars and Clickable Bivalent Polyethyleneglycols. Issue 32 (7th July 2014) - Székely, György; Schaepertoens, Marc; Gaffney, Piers R. J.; Livingston, Andrew G.
Abstract A new strategy to access highly monodisperse, heterobifunctional linear polyethylenglycols (PEGs) has been designed. This was built around unidirectional, iterative chain extension of a 3‐arm PEG homostar. A mono‐(4, 4′‐dimethoxytriphenylmethyl) octagol building block, DmtrO‐EG8‐OH, was constructed from tetragol. After six rounds of chain extension, the monodisperse homostar reached the unprecedented length of 56 monomers per arm (PEG2500). The unique architecture of the synthetic platform greatly assisted in facilitating and monitoring reaction completion, overcoming kinetic limitations, chromatographic purification of intermediates, and analytical assays. After chain terminal derivatisation, mild hydrogenolytic cleavage of the homostar hub provided heterobifunctional linear EG56 chains with a hydroxyl at one end, and either a toluene sulfonate, or a tert‐butyl carboxylate ester at the other. A range of heterobifunctional, monodisperse PEGs was then prepared having useful cross‐linking functionalities (‐OH, ‐COOH, ‐NH2, ‐N3) at both ends. A rapid preparation of polydisperse PEG homostars, free of multiply cross‐linked chains, is also described. The above approach should be extendable to other high value oligomers and polymers.